2021
DOI: 10.1002/adma.202006577
|View full text |Cite
|
Sign up to set email alerts
|

An Air‐Stable and Li‐Metal‐Compatible Glass‐Ceramic Electrolyte enabling High‐Performance All‐Solid‐State Li Metal Batteries

Abstract: All-solid-state lithium metal batteries (ASSLMBs) have been regarded as ideal energy storage devices because of their potential to maximize energy density and improve safety. [1-3] As a key part of ASS-LMBs, the development of solid-state electrolytes (SSEs) has drawn increasing attention. [4,5] Among the various types of SSEs, the inorganic glass-ceramic SSE is one of the most promising categories. [6,7] Apart from the advantages of high ionic conductivity and superior mechanical properties in comparison to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 48 publications
5
74
0
Order By: Relevance
“…The annealed Li 6 PS 5 I shows strong and high-contrast peaks, indicating that post-annealing can synthesize pure argyrodite phase. While for the ball-milled samples, broadened peaks as well as halo backgrounds can be observed, which is very similar to the reported glass-ceramic Li 3 PS 4 and Li 7 P 3 S 11 electrolytes, [39][40][41] suggesting that the electrolytes prepared by UEMA method have partially crystallized small grains within amorphous matrix, named as glass-ceramic argyrodites. According to the Scherrer equation, [42] the mean crystallite size of the LPSI 1+x -gc is ≈15 nm.…”
Section: Resultssupporting
confidence: 83%
“…The annealed Li 6 PS 5 I shows strong and high-contrast peaks, indicating that post-annealing can synthesize pure argyrodite phase. While for the ball-milled samples, broadened peaks as well as halo backgrounds can be observed, which is very similar to the reported glass-ceramic Li 3 PS 4 and Li 7 P 3 S 11 electrolytes, [39][40][41] suggesting that the electrolytes prepared by UEMA method have partially crystallized small grains within amorphous matrix, named as glass-ceramic argyrodites. According to the Scherrer equation, [42] the mean crystallite size of the LPSI 1+x -gc is ≈15 nm.…”
Section: Resultssupporting
confidence: 83%
“…in a Li 3.2 P 0.8 Sn 0.2 S 4 glass–ceramic. [ 161 ] The usage of mechanochemical synthesis again demonstrates how the kinetic energy transfer enables the formation of metastable compounds and local structures that are not accessible via classic solid‐state routes.…”
Section: The Beneficial or Detrimental Influence Of Mechanochemistry In Solid Electrolytesmentioning
confidence: 99%
“…Then, the optimum As-doped Li 3.833 Sn 0.833 As 0.166 S 4 possessed a high conductivity of 1.39 Â 10 À3 S cm À1 at 25 C. 57 In addition, Sn 4+ -doped glass-ceramic Li 3.2 P 0.8 Sn 0.2 S 4 showed strong resistance to H 2 O in 5% humidity air, benefiting from the (P/Sn)S 4 tetrahedron structure. 98 Sun et al 99 reported the strong Sn S bond in Li 6.2 P 0.8 Sn 0.2 S 5 I stabilized crystal structure and improved air stability when exposed to air. Liang et al reported that Li 10 Ge(P 0.025 Sb 0.075 )S 12 exhibited a good air stability of sulfide SSEs due to the softer acid Sb 5+ through HSAB theory.…”
Section: Sulfide-based Ssesmentioning
confidence: 99%